Thermoluminescence in Pure and Nd+3 + K+ Doped Lead Germanate Single Crystals - Wazalwar, Aarti (International Journal Of Chemistry, Mathematics And Physics(IJCMP), 2021)
Pure lead germanate was grown by Zochralski’stechnique.Nd+3 + K+ doped lead germanate was grown for comparative studies. Thermoluminescence studies were conducted on pure lead germanate and Nd+3 + K+ doped lead germanate. Thermoluminescence in pure lead germanate single crystals (LG) and Nd+3 + K+ doped lead germanate single crystals (DDLG) has been measured in terms of photomultiplier output current on Thermoluminescence Set Up. Thermoluminescence studies of LG revealed an increasing trend of Thermoluminescence output, with increasing temperature and sharp consistent maxima at 50°C and 100°C. TL studies of DDLG revealed a decreasing trend of Thermoluminescence output, with increasing temperature and a sharp consistent peak at 100°C and 120°C. It was further noted that doping increased Thermoluminescence output. Thermoluminescence in ferroelectric lead germanate was attributed to change in polarization with change in temperature and creation of defect states.